(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Moringa oleifera is an important traditional medicinal plant usedfor the treatment of many health problems.It is widely cultivated across the world but it has not well known orwell-studied in Iraq. Therefore, the aimof this study is to identify the bioactive compounds present in acetone:methanol (1:1) seeds extractof IraqiMoringa olieifera by using GC-Mass Spectrophotometry.The results of this analysis revealed 41 compounds which include ,terpenes ( cis-beta-Ocimene 0.97%,Cedrene 0.20%, Cedrenol 1.40%, Verrucarol 0.29 , Dehydroxy-isocalamendiol 0.09% , beta-Myrcene0.14% , 3-Thujene 0.06%, Ocimene 0.72% , Sabinene 0.37% Aromadendrene 1.54%) , phenols (0.34%,Eugenol 0.49%, cis-Isoeugenol 1.21%, Methoxyeugenol 0.26%, Ferrocene 0.57%, Phenol, 2-methoxy-4-(1-propenyl)-, (Z) 0.34 , Oxabicyclo[3.3.0]octan-2-one -7-neopentylidene) 0.61% ) , fatty acid methyl esters( n-Tridecanoic acid 0.15% , Undecanoic acid 0.09% , Pentadecanoic acid 34.43%, 4-Hexadienal 1.52% ,Dodecanoic acid 11.02% , cis-Vaccenic acid 21.39%, Hexadecenoic acid 0.15% , Eicosanoic acid 0.03%), acid(myristicin,7.8%), Phenyl propanoid (Asarone, 4.99%), Antioxidant (-tert-Butyl-4-hydroxyanisole, 1.38%),Drug (Berbine, 2,3,9,10-tetramethoxy, 0.73%), Drug (Thiazolo, 0.63%), aldehyde (Trimethylsilyl vanillin,0.61%), hormone (Octenoic acid, 0.46%), Amine (ethyl ester, 0.42%), Carboxylic acid (Dimethylandrost5-en-3-one, 0.28%), Terpenoid (Lavandulol, 0.19%), Heterocyclic compound (Buten-3-one, 1-(2-carboxy4,4-dimethylcyclobutenyl, 0.18%), Volatile oil (Butanoic acid, 0.16%), Fatty alcohol (1-Heptatriacontanol,0.12%), Hydroxy carbon-alkene-(Carene, 0.11%).It can be concluded from this study that the seeds are considered a rich source of bioactive compounds.